(untitled) (Innovative professional education, 2023)
Youth entrepreneurship is one of the important elements of the development of the market economy, which largely contributes to the intensive development of the country, largely determines the rate of economic growth, the quality and structure of the gross national product. In the professional education system, due attention is not paid to the identification of students’ individual qualities of a successful entrepreneur and the development of entrepreneurship as an initiative, innovative, creative and independent activity. In the preparation of students of professional education to start their own business, it is important, first of all, to develop the ability for entrepreneurial activity, which is specified by the presence of strong character qualities. It is necessary to develop the theory and practice of evaluating economic activity as one of the most important methods of scientific management of the economy of enterprises. In the conditions of the market mechanism of management, the analysis is obliged not only to provide an effective assessment of the implementation of plans and the dynamics of production, trade, financial, economic and other activities of companies, but also to find, research and collect reserves of financial and social development, to help make decisions: optimally tactical and strategic management